A non-linear association of low-density lipoprotein cholesterol with all-cause and cardiovascular mortality among patients with hypertension - Liang, Guoliang; Zhang, Wenhao; Gu, Xinxin; Zhang, Qiong; Liu, Ankang; Qing, Xinran; Ma, Jiangwei (Frontiers in Cardiovascular Medicine, 2024)
BackgroundAlthough a few studies have examined the correlation between low-density lipoprotein cholesterol (LDL-C) and mortality, no study has explored these associations in hypertensive populations. This study aims to investigate the relationship between low-density lipoprotein cholesterol and cardiovascular and all-cause mortality in adults with hypertension.MethodsHypertensive participants aged ≥18 years from the National Health and Nutrition Examination Survey 1999–2018 with blood lipid testing data and complete follow-up data until 31 December 2019 were enrolled in the analysis. Univariate and multivariate Cox regression were conducted for the calculation of hazard ratios and 95% confidence intervals. A restricted cubic spline curve was performed to visually represent the relationship between LDL-C and mortality. Kaplan–Meier survival analysis and stratification analysis were also carried out.ResultsWe finally analysed a cohort of 9,635 participants (49.6% male, mean age of 59.4 years). After a median follow-up of 98 months, there were 2,283 (23.7%) instances of all-cause fatalities, with 758 (7.9%) cases attributed to cardiovascular disease. Multivariate Cox regression analysis showed that lower levels of LDL-C were associated with a higher risk of all-cause and cardiovascular mortality; the LDL-C group’s lowest level (<2.198 mmol/L) still showed a 19.6% increased risk of all-cause mortality (p = 0.0068) in the model that was completely adjusted. Both all-cause mortality and cardiovascular mortality showed a non-linear association with LDL-C concentration in restricted cubic spline regression analysis.ConclusionsIn individuals with hypertension, LDL-C was linked to cardiovascular and all-cause mortality. It was further demonstrated that this relationship was non-linear.